Economic Analysis of the Production of Eggplant (Solanum melongena L.) in Two Producing Areas of the Colombian Caribbean: Sucre Savannas and Sinú Valley in Córdoba - Martínez-Reina, Antonio María; Tordecilla-Zumaqué, Lilibet; Grandett-Martínez, Liliana María; Rodríguez-Pinto, María del Valle; Cordero-Cordero, Carina Cecilia; Silva-Acosta, Gabriel Ernesto; Romero-Ferrer, Jorge Luis; Correa-Álvarez, Ender Manuel; Orozco-Guerrero, Alfonso Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper describes the socioeconomic and technological characteristics of the eggplant production system in the microregions of the Sinú Valley and Sucre Savannas in Colombia. Through the simple random sampling technique, we selected 62 farmers. It was collected data using a formal structured survey previously tested and analyzed.  Small producers plant the crop in an average area of ​​0.6 hectares. The average age is 53 years with more than 30 years of experience in cultivation. It is less expensive to produce eggplant in the state of Sucre than in Córdoba, due to the proportion in which labor is involved in production costs, because they are higher for Sucre State with 75% of the total costs, on the contrary, in Córdoba State the labor force participates in 63%. The net income is higher in the case of Córdoba owing to the difference in yields, which are 35 t/ha-1 while for Sucre they are 25 t/ha-1. With regard to marketing margins, for each monetary unit that the consumer pays, $ 0.82 constitutes profits that are in the intermediation chain distributed. The participation of 53 % intermediation is very high. We conclude that the farmer is the one who risks the most and who receives the least from this difference in the price between the farmer and the final consumer.